Effectiveness of feeding supplementation in preterm infants: an overview of systematic reviews - Keqin Liu; Jiaxin Tao; Jixin Yang; Yufeng Li; Yanwei Su; Jing Mao (BMC, 2022)
Abstract Background Preterm infants have higher nutrition needs than term infants. The effectiveness of various feeding supplementation was assessed by the improvement of health outcomes in single specific systematic reviews (SRs). The aim of this review was to comprehensively describe the effectiveness of feeding supplementation in promoting health outcomes of preterm infants. Methods A literature search was conducted in the PUBMED, EMBASE, Science Direct, Cochrane library, Web of Science, and Wiley online library. SRs selection followed clear inclusion and exclusion criteria. Pairs of reviewers independently applied the criteria to both titles/abstracts and full texts. Screening and data extraction were performed by using the advanced tables. The methodological quality of SRs and the quality of the evidence were carried out according to the Assessing the Methodological Quality of Systematic Reviews (AMSTAR) tool and the Grades of Recommendation, Assessment, Development, and Evaluation guidelines (GRADE) respectively. A qualitative synthesis of evidence is presented. Results Seventeen SRs were included in the review. Fifteen kinds of feeding supplementation were reported in the SRs. In preterm infants, the effectiveness of feeding supplementation in addition to regular breast-feeding was mainly shown in six aspects: physical health, neurodevelopment, biochemical outcomes, other health outcomes, morbidity and all-cause mortality. And the effectiveness of the interventions on health outcomes in preterm infants was found by most systematic reviews. The methodological quality of all the included SRs was high, and most of the evidences was of low or very low quality. Conclusions Our results will allow a better understanding of the feeding supplementation in preterm infants. Although the feeling supplements may improve the health outcomes of in preterm infants, the existing evidence is uncertain. Therefore, the clinical use of these supplements should be considered cautiously and more well-designed RCTs are still needed to further address the unsolved problems of the included SRs.